Retrospective Evaluation of Patients with Systemic Juvenile Idiopathic Arthritis: A Single-centre Experience - Bağlan, Esra; Özdel, Semanur; Güngör, Tülin; Çelikkaya, Evra; Karakaya, Deniz; Bülbül, Mehmet (Aktuelle Rheumatologie, 2021)
Objective Systemic juvenile idiopathic arthritis is one of the subtypes of juvenile idiopathic arthritis. This type of disease accounts for approximately 10–20% of all cases of juvenile idiopathic arthritis. It typically affects both sexes equally and is usually present in children under 5 years. This study aimed to evaluate the demographic and clinical features of patients who were followed up for the diagnosis of sJIA in a single centre, the treatments they received, the responses to the treatment and the course of the disease.Methods All patients with systemic juvenile idiopathic arthritis who were evaluated at Dr Sami Ulus Maternity Child Health and Diseases Training and Research Hospital, Department of Paediatric Rheumatology, between January 2017 and January 2020 were included in this study. Descriptive features, clinical information, medications, treatment responses and long-term prognosis of patients were evaluated retrospectively.Results The study included 40 patients. 60% (n=24) of the patients were female and 40% (n=16) were male. The diagnosis age of the patients was 7.77±4.82 years and the patients were followed up for an average of 48±41 months. All of the patients had fever at the time of diagnosis. The 3 most common clinical signs after fever were arthralgia, hepatomegaly and lymphadenopathy (65, 55 and 50%, respectively). Ten patients (32.5%) had macrophage activation syndrome at admission. No significant difference was detected between the groups with and without macrophage activation syndrome concerning age, gender and clinical findings. Leukocyte, haemoglobin, platelet and erythrocyte sedimentation rates were significantly lower in the macrophage activation syndrome group compared with the other group, and ferritin was significantly higher. The C-reactive protein value was higher in the group without macrophage activation syndrome, but the difference was not statistically significant. While all patients received corticosteroid therapy as the initial therapy, 87.5% of these patients were administered pulse methylprednisolone therapy. In the follow-up, 21 patients (52.5%) needed biological treatment. Twenty-seven patients (67.5%) had a monocyclic course, 3 patients (7.5%) had a polycyclic course and 10 patients (25%) had a persistent polyarticular course.Conclusion Early diagnosis and treatment of systemic juvenile idiopathic arthritis are important because of the risk of developing macrophage activation syndrome – the most lethal complication. In our evaluation, it was seen that laboratory parameters could provide more guidance than clinical findings. Although steroids are the cornerstone of therapy, biological agents are effective in patients who are not responsive to steroid therapy.Hintergrund Die systemische juvenile idiopathische Arthritis ist ein Subtyp der juvenilen idiopathischen Arthritis. Auf diesen Krankheitstyp entfallen etwa 10 bis 20% aller Fälle von juveniler idiopathischer Arthritis. Er betrifft üblicherweise beide Geschlechter gleichermaßen und tritt in der Regel bei Kindern unter fünf Jahren auf. Ziel dieser Studie war die Bewertung der demografischen und klinischen Merkmale der in einem einzigen klinischen Zentrum mit sJIA diagnostizierten Patienten sowie deren Behandlungen, Reaktionen auf die Behandlung und Krankheitsverlauf.Methoden Alle zwischen Januar 2017 und Januar 2020 in der Abteilung für pädiatrische Rheumatologie des Dr.-Sami-Ulus-Kinderkrankenhauses untersuchten Patienten mit systemischer juveniler idiopathischer Arthritis wurden in diese Studie eingeschlossen. Deskriptive Merkmale, klinische Informationen, Medikamente, Ansprechen auf die Behandlung und die Langzeitprognose der Patienten wurden retrospektiv ausgewertet.Ergebnisse In diese Studie wurden 40 Patienten eingeschlossen. 60% (n=24) der Patienten waren weiblich und 40% (n = 16) waren männlich. Das Diagnosealter der Patienten lag bei 7,77 ± 4,82 Jahren, und die Patienten wurden durchschnittlich 48 ± 41 Monate nachbeobachtet. Alle Patienten hatten zum Zeitpunkt der Diagnose Fieber. Die drei häufigsten klinischen Symptome nach Fieber waren Arthralgie (65%), Hepatomegalie (55%) und Lymphadenopathie (50%). Zehn der Patienten (32,5%) hatten bei Aufnahme ein Makrophagenaktivierungssyndrom. Es wurde kein signifikanter Unterschied zwischen den Gruppen mit und ohne Makrophagenaktivierungssyndrom in Bezug auf Alter und Geschlecht sowie klinische Befunde festgestellt. Die Erythrozytensedimentationrate von Leukozyten, Hämoglobin, Blutplättchen und Erythrozyten war in der MAS-Gruppe im Vergleich zur anderen Gruppe signifikant niedriger und der Ferritinspiegel war signifikant höher. Die Konzentration des C-reaktiven Proteins war in der Gruppe ohne Makrophagenaktivierungssyndrom höher, doch diese Erhöhung war statistisch nicht signifikant. Laborparameter scheinen wichtiger zu sein als klinische Befunde. Alle Patienten erhielten als Ersttherapie eine Kortikosteroidtherapie, 87,5% von ihnen wurde eine Methylprednisolon-Stoßtherapie verabreicht. In der Nachuntersuchung benötigten 21 Patienten (52,5%) eine biologische Behandlung. 27 Patienten (67,5%) zeigten einen monozyklischen, 3 Patienten (7,5%) einen polyzyklischen und 10 Patienten (25%) einen persistierenden polyartikulären Verlauf.Schlussfolgerung Eine frühzeitige Diagnose und Behandlung der systemischen juvenilen idiopathischen Arthritis ist wichtig, da das Risiko besteht, ein Makrophagenaktivierungssyndrom zu entwickeln – die tödlichste Komplikation. In unserer Bewertung wurde festgestellt, dass Laborparameter richtungsweisender sein können als klinische Befunde. Obwohl Steroide den Eckpfeiler der Therapie darstellen, sind biologische Wirkstoffe bei Patienten wirksam, die nicht auf eine Steroidtherapie ansprechen.
Keywords: biological agents; macrophage activation syndrome; systemic juvenile idiopathic arthritis